Urgency of Cultural and Citizen Literacy for Elementary School in the Digitalization Era - Indra Kurniawan, Machful; Wardana, Mahardika Darmawan Kusuma; Wulandari, Ria (Universitas Muhammadiyah Sidoarjo, 2022)
Starting to fade awareness of the diversity that exists in the social environment, will result in conflicts between individuals and between groups emerging. The emergence of these conflicts has an impact on disrupting national stability because it is easier for people to be divided with hatred and prejudice just because they do not know and understand the diversity of their nation, especially in the digitalization era which provides easy access to digitally interacting, therefore the implementation of cultural literacy and citizenship in the current digital era, it is very necessary to implement it in the world of education, especially at the elementary school level which is a basic means in developing student potential to become human beings who believe and are devoted to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent. , and become a democratic and responsible citizen. This study aims to describe the urgency of cultural literacy and citizenship for elementary schools in the digitalization era and how to implement cultural literacy and citizenship in elementary schools. This research uses a literature study method by collecting and analyzing various literature sources such as books, magazines, and research journals that are in accordance with the research objectives. Based on the results of the study, it was found that in the current digitalization era, the implementation of cultural literacy and citizenship in elementary schools is very urgent. The implementation of cultural literacy and citizenship in elementary schools can be carried out well if it is supported by parents, and the surrounding community by providing facilities to support cultural and civic literacy programs prepared by the school.